THE INFLUENCE OF FINANCIAL LITERACY AND MULTIDIMENSIONAL RISK ON INVESTMENT DECISIONS OF SHARIA INVESTORS IN THE CAPITAL MARKET - Syahidah, Hilyah; Mutasowifin, Ali (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The development of the Islamic capital market in Indonesia shows great potential, but investor participation is still relatively low. This study aims to analyze the influence of financial literacy and multidimensional risk on investment decisions in the Islamic capital market. Multidimensional risk in this study includes risk propensity, risk attitude, risk capacity, and risk knowledge. The research was conducted at the Ulive Education Center Islamic Investment Gallery, which has been actively providing Islamic-based investment education. The method used was quantitative with a Partial Least Squares Structural Equation Modeling ( PLS-SEM) approach, based on data from 140 respondents who had invested at least once. The results showed that financial literacy, risk attitude, risk capacity, and risk knowledge had a positive and significant effect on investment decisions. Meanwhile, risk propensity showed a positive but insignificant effect. These findings emphasize the importance of improving financial literacy and risk understanding to encourage wise investment decisions in the Islamic capital market.